The effects of apocynin on monosodium glutamate induced liver damage of rats - BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2023)
Monosodium glutamate (MSG) is found in refined foods. Apocynin (APO) is a selective NADPH oxidase (NOX) inhibitor. The aim of this experimental study was to investigate possible effects of MSG and the curative effects of APO in rats. Twenty-eight male Sprague-Dawley rats were randomly divided into four groups (Normal control, APO, MSG and MSG + APO, n:7 for each group). The MSG and MSG + APO groups received 120 mg/kg MSG solution orally for 28 consecutive days. The APO and MSG + APO groups received 25 mg/kg APO solution orally for 5 days until the end of the experiment. At the end of the experiment, all rats were sacrificed and liver tissue and blood samples were taken for histological, ultrastructural, and biochemical analyses. In the MSG group, vacuolization and loss in glycogen content in the hepatocytes, leukocyte infiltration and fibrosis in the liver parenchyme and portal triads, were observed. Terminal deoxynucleotidyl transferase dUTP (TUNEL)-positivity and NADPH oxidase (NOX)-2-positivity were higher in the MSG group compared with the other experimental groups. The concentrations of alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), total bilirubin, malondialdehyde (MDA), and myeloperoxidase (MPO) were higher, whereas albumin, glutathione (GSH), and superoxide (SOD) levels were lower in the MSG group. All these data has been reversed in MSG + APO group. The histological and biochemical criteria indicated the prominent ameliorating effect of APO on MSG -induced liver injury.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE